Pseudopollen in Camellia oleifera and its implications for pollination ecology and taxonomy - Yuan, Bin; Yuan, Jing-Kun; Huang, Cheng-Gong; Lian, Jia-Rui; Li, Yi-Huan; Fan, Xiao-Ming; Yuan, De-Yi (Frontiers in Plant Science, 2022)
Background and Aims: In 1997, Tsou described the special differentiation of the connective tissues of some species of Theaceae to produce single-celled powders with unique patterns called pseudopollen. The purpose of this study was to investigate the morphological structure of the pseudopollen of Camellia oleifera (Theaceae). Methods: Scanning electron microscopy, paraffin section, light microscopy, transmission electron microscopy, histochemistry. Key Results: C. oleifera pseudopollen was similar to normal pollen in macroscopic morphology but different microscopically. The normal pollen was starch-rich and yellow, with grid ornamentals on the outer wall. In contrast, the pseudopollen was a white powder, single-celled and rich in protein, with parallel unbranched ridge lines on the outer wall, and originated from the parenchyma of the connective tissues. There are also differences in the micro-characteristics of normal and pseudopollen among different species in Camellia. Conclusion: There are great differences in morphological structure between C. oleifera and other species in Camellia normal pollen and pseudopollen; this may indicate that the pseudopollen can be used as a taxonomic basis for Camellia, and it can be a pollination strategy.